Analysis of performances of European Championship participants among women`s wrestling cadets - Latyshev, M.; Rybak, L.; Holovach, I.; Korolov, B.; Liashenko, O.; Kvasnytsya, O. (Slobozhanskyi herald of science and sport, 2019)
Purpose: to analyze the sports achievements of the participants of the European Championships among cadets in women's wrestling for the national team of Ukraine.